Biological control of sheep parasite nematodes by nematode-trapping fungi: In vitro activity and after passage through the gastrointestinal tract - Graminha, Érika B. N. [UNESP]; Costa, Alvimar J. [UNESP]; Oliveira, Gilson P. [UNESP]; Monteiro, Antonio C. [UNESP]; Palmeira, Solange B. S. [UNESP] (Springer Nature, 2005)
The main method used for the control of gastrointestinal nematodes in sheep production is the application of chemotherapeutic agents, which often lead to the selection of parasites resistant to given active principles. Biological control can be considered a promising alternative, contributing to an increase in the efficacy of verminous control. We determined the in vitro activity and in situ survival of the predatory fungi Arthrobotrys musiformis and Arthrobotrys conoides during passage through the gastrointestinal tract of sheep after oral administration of conidia in microencapsulated form and as a liquid in natura. Initial in vitro tests showed that both fungi were efficient in the predation of trichostrongylid L3 larvae present in the faeces of sheep naturally infected with gastrointestinal nematodes. The fungi presented high nematophagous activity, which was 99.3% for A. conoides and 73.7% for A. musiformis. A. conoides did not survive passage through the gastrointestinal tract under the conditions of the present experiment. On the other hand, A. musiformis was reisolated after administration in either microencapsulated or liquid form, suggesting that this species is a promising alternative for the control of nematodes in sheep since it survives without any protection (in natura). © Springer 2005.
Keywords: Arthrobotrys conoides; Arthrobotrys musiformis; Nematodes; Nematophagous fungi; Sheep; Biocontrol; Biodiversity; Biological organs; Fungi; Growth kinetics; Pathology; Biological control; Parasites; Sheeps; Microorganisms; Nematoda; Ovis aries; Trichostrongylidae